A Synthesis of Povidone-Iodine-Based Polymeric Nanoparticles for Intrauterine Applications - Jaber, Ali Habeeb; Kridi, Salah Mahdi (American Journal of Biomedicine and Pharmacy, 2025)
The present study investigates the synthesis and assessment of povidone-iodine-based polymeric nanoparticles (PVP-I-NPs) for potential application in the management of intrauterine uses. N-vinyl-2-pyrrolidone and methyl methacrylate used as a copolymer to create the nanoparticles. Iodine loading in ethanol was the next step in the production process, which involves free radical polymerization. They used UV-Vis spectroscopy, FTIR, SEM for characterization and Toxicity. The particles’ diameters ranged from around 310 to 500 nm, according to the SEM examination. FTIR data demonstrated that iodine and the polymer successfully bound together by confirming the presence of distinctive functional groups. According to UV-Vis analysis, there were absorption peaks at 247 and 259.5 nm in line with iodine-polymer interactions-induced electronic transitions. Cytotoxicity experiments on CHO cell lines showed little adverse effects, confirming the nanoparticles’ safety and suitability for biological uses. Accordingly, these results, confirmed that PVP-I-NPs is provided a useful substitute method for intrauterine antibiotic treatment. However, additional research is needed to explore the vivo effectiveness and reproductive outcomes to treat complication inflammation of the female reproductive system in comparison with antibiotics and bacterial resistance.